2011
DOI: 10.1007/s11071-011-0071-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient parametric excitation walking with delayed feedback control

Abstract: In passive dynamic walking proposed by McGeer, mechanical energy lost by heel strike is restored by transporting potential energy to kinetic energy as walking down a slope. When energy input is larger as a slope is steeper, the bifurcation of a walking cycle occurs. In the parametric excitation walking, which is to realize passive dynamic-like walking on the level ground, the bifurcation of a walking cycle has also been observed when walking speed is This paper is the completed and extended version of the conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Recently, Asano and Luo 3 studied walking efficiency related to bifurcations. Harata et al 12 showed that the gait efficiency can be improved by changing the periodic gaits from period-2 to period-1 gaits using delayed feedback control.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Asano and Luo 3 studied walking efficiency related to bifurcations. Harata et al 12 showed that the gait efficiency can be improved by changing the periodic gaits from period-2 to period-1 gaits using delayed feedback control.…”
Section: Introductionmentioning
confidence: 99%
“…In hybrid systems and especially systems that encounter jump and impact events, chaotic dynamics may happen [9,24]. Also, in hybrid dynamics, stability and control are the critical issues for studying [25][26][27].…”
Section: -Introductionmentioning
confidence: 99%
“…In hybrid systems and especially the systems that encounter to impact event, a chaotic dynamics may be happened. Some studies are done in this field [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%